Diseminasi Teknologi Mesin Feed Grinder dan Pelatihan Pembuatan Silasi Berbahan Limbah pertanian untuk Menghasilkan Pakan Domba Bernutrisi - Widiyanti; Didik Nurhadi; Wiwik Wahyuni; Robby Wijaya; Leny Suryani; Indra Febrianto; Umniyah Juman Rosyidah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This community service activity aims to disseminate feed grinder machine technology and provide training on making silage from agricultural waste as an alternative, nutritious feed for sheep in collaboration with the Sumber Mendho Nusantara livestock group. The implementation method involves four stages: preparation, which focuses on identifying the partner's problems and needs; training, which includes socializing the use of agricultural waste and demonstrating the feed grinder machine; mentoring, which focuses on follow-up and monitoring previous activities; and reporting and sustainability to ensure that the program continues to be implemented by the partner. The outcomes of this community service are that the partners are able to understand and apply appropriate technology to process waste, such as cassava and corn cobs, into quality feed. This activity not only reduces the farmers' dependence on commercial feed but also increases operational efficiency and opens up new opportunities in agropreneurship. The results also indicate a positive change in the partners' mindset, skills, and ability to manage agricultural waste. Furthermore, the increased knowledge of operating and maintaining appropriate technology provides a strong foundation for the program's sustainability in the future. With the support of proper technology and training, the livestock group can improve the quality of animal feed and optimize local economic potential.